Development of Edugame-Based 'Math Quest' Learning Media to Improve Elementary School Students' Mathematical Skills in Fractional Materials through Interactive Learning - Putra, Febrinta Bima Permata; Primasatya, Nurita; Putri, Kharisma Eka; Damariswara, Rian (Sahabat Publikasi, 2025)
Mathematics learning in elementary schools, especially in fractional materials, still faces significant challenges where around 70% of students show a passive attitude and lack of enthusiasm in the learning process. This research aims to develop an edugame-based 'MathQuest' learning media to improve the mathematics skills of elementary school students through an interactive learning approach. The research method uses Research and Development (R&D) with the ADDIE model which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The research was carried out at SDN Samar 1 with 30 subjects of 5th grade students, which were divided into a limited test group (10 students) and a broad test (20 students). The research instruments included expert validation sheets, teacher and student response questionnaires, and learning outcome tests. The results of the study showed that MathQuest learning media met the criteria very valid with a media expert validation score of 92.5% and a material expert validation score of 91.6%. From the practical aspect, the media obtained a score of 94% from teachers and 90% from students, indicating the category of very practical. The effectiveness test through the post test resulted in a score of 87.7% on the limited test and 90% on the broad test, indicating that the media is very effective in improving students' mathematical understanding. MathQuest succeeds in creating more interactive, engaging, and fun learning by combining educational elements and game features that motivate students to learn independently and think critically. This media can be implemented as an innovative solution to support the goals of mathematics learning in elementary schools that are relevant to the development of educational technology.